MANAGEMENT OF ISLAMIC EDUCATION MANAGEMENT (MPI) GRADUATES COMPETENCE IMPROVEMENT THROUGH MADRASA INTERNSHIP IN MPI UIN SUNAN GUNUNG DJATI BANDUNG - Badrudin Badrudin (Edukasi Islami : Jurnal Pendidikan Islam, 2020)
This research aims to know and analyze the implementation of the internship/PLP program of Islamic Education Management (MPI) students at the Faculty of Tarbiyah and Teacher Training of UIN Sunan Gunung Djati Bandung. PLP/Internship is expected to improve the competence of MPI graduate students as candidates for prospective educators or educational professionals. Therefore, students, as one component in the development of educational institutions, need to understand and comprehend the context of empowerment and management of madrasas thoroughly. This research uses a qualitative case study method with natural paradigm. Data collection techniques are conducted by interview, observation, and document studies. The results of the research indicated that the internship / PLP program can improve the student capacity which includes improving personality, social, technique and managerial competencies. Students are able to manage and explore themselves in implementing various programs to advance Islamic Educational institutions (madrasas). On the other hand, students also need reinforcement and motivation to implement the internship program as a whole and efficiently.